2013
DOI: 10.1002/per.1847
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Stability and Affective Self–regulatory Efficacy Beliefs: Proofs of Integration between Trait Theory and Social Cognitive Theory

Abstract: The present study aimed to investigate the development and interplay of emotional stability and affective self‐regulatory efficacy beliefs through adolescence to young adulthood. A latent growth curve approach was used to investigate level and stability of emotional stability and self‐efficacy in managing negative emotions and in expressing positive emotions. We found that initial levels of emotional stability and self‐efficacy beliefs are highly correlated. In accordance with the posited hypothesis, the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 53 publications
5
68
0
12
Order By: Relevance
“…They accept as reflects the basic trend the organization of feeling, behavior and thinking (McCrae and Costa, 2008). Personality traits are sustained potential susceptibility that reveal a person's actions alarming (Caprara, Vecchione, Barbaranelli and Alessandri, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They accept as reflects the basic trend the organization of feeling, behavior and thinking (McCrae and Costa, 2008). Personality traits are sustained potential susceptibility that reveal a person's actions alarming (Caprara, Vecchione, Barbaranelli and Alessandri, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is unexpected, but perhaps can be understood through the lens of social cognitive theory; one's perceptions of mental health problems contrast with the realistic implications of the problems on their behavioral outcomes. Scholars have talked about the notion of the social construction of cognition and how one's perception, while considered their "truth" may in all actuality be juxtaposed with reality (Caprara, Vecchione, Barbaranelli, & Alessandri, 2013). In fact, some research has revealed that it may be more common for youth to have "self-serving cognitive distortions" relative to adults that link to antisocial behavior (Wallinius, Johansson, Lardén, Dernevik, 2011, p. 288).…”
Section: Discussionmentioning
confidence: 99%
“…Kişilik teorileri, kişiliği; bireyin yapabileceği veya ulaşabileceği potansiyellerini açığa çıkarmasına yardımcı olacak ve temel eğilimlerini yansıtan duygu, davranış ve düşüncelerinin organizasyonu olarak kabul etmektedirler (McCrae ve Costa, 2008). Kişilik özellikleri, kişinin uyarıcılar karşısında ortaya koyacağı eylem ve süreğen potansiyel yatkınlıklardır (Caprara, Vecchione, Barbaranelli ve Alessandri, 2013).…”
unclassified